When low interest rates cause low inflation - Markus Demary; Michael Hüther (Intereconomics, 2015)
A new theory of interest rates, the Neo-Fisherian theory, predicts a low inflation rate due to a central bank's low interest rate. After several years of near-zero interest rate policies and low and even negative infl ation rates in the eurozone and in the US, this theory gained momentum in academic circles. Indeed, central banks have had a hard time reaching their infl ation targets. This paper argues that it is not the low central bank policy rate which causes low inflation but rather the low equilibrium real interest rate, the economy's real interest rate under full employment and stable prices, in combination with the zero lower bound on nominal interest rates, which restricts the effectiveness of monetary policy and causes low infl ation. In order to stabilise infl ation in the medium term, higher equilibrium real interest rates are necessary. Since monetary policy cannot move the equilibrium real interest rate, structural policies are needed.
Keywords: 330; Konsumtheorie; Einkommenshypothese; Niedrigzinspolitik; Inflationsrate